Inhibition of the TGFβ signalling pathway by cGMP and cGMP‐dependent kinase I in renal fibrosis. Issue 4 (1st March 2017) - Schinner, Elisabeth; Wetzl, Veronika; Schramm, Andrea; Kees, Frieder; Sandner, Peter; Stasch, Johannes‐Peter; Hofmann, Franz; Schlossmann, Jens
Abstract : Agents that enhance production of nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) ameliorate the progression of renal fibrosis. However, the molecular mechanism of this process is not fully understood. We hypothesize that the antifibrotic effects of cGMP and cGMP‐dependent kinase I (cGKI) are mediated via regulation of the TGFβ signalling pathway, both via ERK and the Smad‐dependent route. Kidney fibrosis was induced by unilateral ureter obstruction (UUO) in wild‐type and cGKI‐deficient (cGKI‐KO) mice. The cGMP/cGKI signalling pathway was activated by application of the soluble guanylate cyclase (sGC) stimulator BAY 41‐8543 (BAY), beginning 1 day after UUO. After 7 days, the antifibrotic effects of BAY were analysed by measuring mRNA and protein expression of characteristic fibrotic biomarkers. The effects of cGMP/TGFβ on cultured fibroblasts were also analysed in vitro . BAY application influenced the activity of the extracellular matrix (ECM)‐degrading matrix metalloproteases (MMP2 and MMP9) and their inhibitor tissue inhibitors of metalloproteinase‐1, the secretion of cytokines (e.g. IL‐6) and the expression pattern of ECM proteins (e.g. collagen, fibronectin) and profibrotic mediators (e.g. connective tissue growth factors and plasminogen‐activator inhibitor‐1). Activation of the cGMP/cGKI signalling pathway showed protective effects against fibrosis which were mediated by inhibition of P‐Erk1/2 and translocation of P‐smad3. The elucidation of these signalling mechanisms might support the development of new therapeutic options regarding cGMP/cGKI‐mediated antifibrotic actions. Abstract : In renal fibrosis, activation of cGMP/cGMP‐dependent kinase I signalling by application of soluble guanylate cyclase stimulator BAY 41‐8543 showed antifibrotic effects by inhibition of P‐Erk1/2 and P‐smad3 translocation. Thereby, BAY influenced the activity of matrix metalloproteases (MMP2 and MMP9), expression pattern of extracellular matrix proteins (collagen, fibronectin) and profibrotic mediators (connective tissue growth factors, plasminogen‐activator inhibitor‐1).